Ordboksbruk i skolen – praksis og perspektiv Utnytting av einspråklege ordbøker i norskfaget i den vidaregåande skolen - Karlsen, Knut E.; Rødningen, Dagfinn (LexicoNordica, 2008)
In the light of curricula in compulsory school and upper-secondary school the authors have investigated how monolingual dictionaries are exploited in Norwegian mother tongue teaching in upper-secondary school by questionnaires from 111 mother tongue teachers. The investigation reveals that 86 percent of the teachers provide training in dictionary use, but that the attention is mainly given to formal information such as spelling and flexion. An investigation of the textbooks used in mother tongue teaching shows that dictionary use is no subject, not even when the matter strongly invites to this.